Implementasi Kebijakan Penanggulangan Bencana Kebakaran Hutan dan Lahan di Kabupaten Ogan Ilir Tahun 2019 - Ajeng Ayu Wulandari; Isabella Isabella; Doris Febriyanti (Universitas Terbuka, 2022)
The purpose of this research is to find out how to implement forest and land fire disaster management policies in Ogan Ilir. The research method used in this research is qualitative research. The results show that by using Edward III's theory to analyze there are four indicators, including Communication, Resources, Disposition, and Birocration. First is communication, information delivery is only in the form of banners and banners that are installed near village settlements. Second, resources are also sufficient to consist of 110 Regional Disaster Management Agency personnel and 28 volunteers. Third, Disposition, this indicator is the lack of responsiveness given by the personnel of the Village Task Force and the Subdistrict Task Force to the community in Palemraya Village when forest and land fires occur. Fourth, Bureaucratic Structure, on this indicator the author finds irregularities in the bureaucratic structure, this can be seen from the disaster management procedures which are too convoluted and a waste of time. Based on the results of the research and discussion, it can be concluded that the Implementation of the Forest and Land Fire Disaster Management Policy in Ogan Ilir Regency in 2019 has gone well although there are several obstacles faced by the Ogan Ilir Regency Regional Disaster Management Agency and the parties in the implementation of the policy. However, all can be overcomed. Suggestions in this study are the Regional Disaster Management Agency of Ogan Ilir Regency can provide socialization to the community, can minimize the flow of procedures in handling fire disasters and the Regional Disaster Management Agency of Ogan Ilir Regency can further improve responsiveness in the field when a fire occurs.